Analysis of the Role of Social Media and Consumer Preferences in Increasing Online Buying Interest of Students of the Faculty of Economics and Business, Udayana University - I Gusti Ayu Ngurah Sindi Sasmita; I Gede Krishna Wiradinatha (PT. Global World Scientific, 2025)
This study aims to analyze the influence of social media and consumer preferences on online buying interest of Package 7 students, Faculty of Economics and Business, Udayana University. The research method used is a quantitative approach with a Likert-scale questionnaire instrument, as well as multiple linear regression analysis. The F test results show a significance value of 0.006 which is smaller than 0.05, so the regression model is declared feasible to use. These results prove that social media variables and consumer preferences simultaneously have a significant effect on online buying interest. Thus, the research model can explain the relationship between variables empirically and is relevant to current digital phenomena. The t-test results show that social media variables have a significant effect with a negative coefficient direction, which means that exposure to certain social media actually reduces online buying interest if not managed properly. Conversely, consumer preferences have a significant effect with a positive coefficient direction, indicating that the stronger consumer preferences, the higher the interest in buying online. The R Square value of 0.387 indicates that the two independent variables are able to explain 38.7% of the variation in online purchase intention. The remaining 61.3% is influenced by other factors outside the model, such as price, product quality, and promotion. This research provides theoretical and practical contributions in digital marketing strategies, especially among the younger generation.